2019
DOI: 10.1088/1755-1315/384/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

The propagation research of hydraulically created fractures in coal seams based on discrete element method

Abstract: Coalbed methane (CBM) is clean unconventional energy that can be exploited with stimulation treatment to realize commercial value, and hydraulic fracturing is the key technology for increasing CBM production. The simulation of hydraulic fractures is an important research content that can guide the engineering practice to achieve the purpose of increasing production. Based on the distribution characteristic of cleats in coal, the research on the propagation of hydraulic fractures is carried out via Discrete ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was found that conglomerate particles affect fracture propagation in two ways, penetration and avoidance, and the penetration pressure of conglomerate strata is linearly and nonlinearly related to particle strength and content, respectively. Based on the advantages of the discrete element method in studying discontinuous structures, Lu et al [110] established a discrete element model to simulate the effect of coal seam cuttings on hydraulic fracture propagation and found that hydraulic fractures mainly extend along the direction of maximum principal stress. In addition to the influence of the developmental characteristics of different rocks on hydraulic fracture propagation, other scholars have analyzed the influence of ground stress difference, fracture interaction, tectonic parameters, and other fundamental features on the hydraulic fracture propagation [111].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…It was found that conglomerate particles affect fracture propagation in two ways, penetration and avoidance, and the penetration pressure of conglomerate strata is linearly and nonlinearly related to particle strength and content, respectively. Based on the advantages of the discrete element method in studying discontinuous structures, Lu et al [110] established a discrete element model to simulate the effect of coal seam cuttings on hydraulic fracture propagation and found that hydraulic fractures mainly extend along the direction of maximum principal stress. In addition to the influence of the developmental characteristics of different rocks on hydraulic fracture propagation, other scholars have analyzed the influence of ground stress difference, fracture interaction, tectonic parameters, and other fundamental features on the hydraulic fracture propagation [111].…”
Section: Discrete Element Methodsmentioning
confidence: 99%